Le financement du secteur de l’huile de palme : pourquoi les institutions financières de développement doivent continuer à investir en Afrique* - Skurtis Thomas; Aïnaché Guédi; Simon Didier (Oléagineux, Corps gras, Lipides, 2010)
Over the past three decades, palm oil has become the leading vegetable oil, a commodity that can be found in a large variety of food and non-food products. Mainly produced in South-East Asia, palm oil has recently been at the centre of many controversies. The industry has sometimes grown in an unsustainable way, with negative environmental and social impacts, among which deforestation, loss of biodiversity, poor working conditions in industrial plantations or land grabbing. In September 2009, the recognition of these issues has led the International Finance Corporation (IFC, member of the World Bank Group) to stop all its investments in the sector worldwide. This example has been followed by most development finance institutions (DFIs) which have put on hold any investment in South-East Asia and are now very cautious in the rest of the world. However, the bad Asian experience should not prevent DFIs from investing in this sector in Africa. The continent lacks from local production despite the importance of this oil in its diet. But palm oil is not only a question of food security. When properly supervised, the industry can also have a significant impact on rural development. It creates local added value and jobs. Palm oil producers often provide social services (heath, education etc.) that Governments do not always offer in remote rural areas. Moreover, through the rehabilitation of old and non performing plantations, the industry has room for an environment friendly growth. It is the role of DFIs to support sponsors of palm oil projects while insisting on their commitment to best practices and the most stringent environmental and social criteria.